Modular synthesis of 2-furyl carbinols from 3-benzyldimethylsilylfurfural platforms relying on oxygen-assisted C–Si bond functionalization - Curpanen, Sebastien; Reichert, Per; Lupidi, Gabriele; Poli, Giovanni; Oble, Julie; Perez-Luna, Alejandro (Beilstein Journal of Organic Chemistry, 2022)
3-Silylated furfurals, readily prepared in three steps from biomass-derived furfural and 5-methylfurfural, are converted into 3-silylated 2-furyl carbinols upon condensation with organomagnesium or organolithium reagents. The hydroxy unit of the carbinol adducts can be exploited to promote C3(sp2)–Si bond functionalization through intramolecular activation. Two approaches were contemplated for this purpose. Activation by alkoxides of the C3–SiEt3 or C3–SiMe2t-Bu bonds was ineffective. Conversely, treatment of the C3-benzyldimethylsilyl-appended derivatives with tetrabutylammonium fluoride led to cyclic siloxanes, which revealed to be competent donors for copper-catalyzed cross-coupling reactions, such as arylation reactions catalyzed by Pd2(dba)3/CuI, as well as allylation and methylation reactions catalyzed by CuI⋅PPh3. C3-Benzyldimethylsilyl-appended furfurals are thus introduced as versatile platforms, providing a modular access to 3-substituted 2-furyl carbinols from renewable feedstock.
Keywords: biomass; copper; cyclic siloxanes; 2-furyl carbinols; silicon

(untitled) - Bender, T. A.; Dabrowski, J. A.; Gagné, M. R. (Nat. Rev. Chem., 2018)

(untitled) - Bozell, J. J.; Petersen, G. R. (Green Chem., 2010)

(untitled) - Mika, L. T.; Cséfalvay, E.; Németh, Á. (Chem. Rev., 2018)

(untitled) - Chen, S.; Wojcieszak, R.; Dumeignil, F.; Marceau, E.; Royer, S. (Chem. Rev., 2018)

(untitled) - Zhang, X.; Xu, S.; Li, Q.; Zhou, G.; Xia, H. (RSC Adv., 2021)

(untitled) - Xu, C.; Paone, E.; Rodríguez-Padrón, D.; Luque, R.; Mauriello, F. (Chem. Soc. Rev., 2020)

(untitled) - Bielski, R.; Grynkiewicz, G. (Green Chem., 2021)

(untitled) - Pezzetta, C.; Veiros, L. F.; Oble, J.; Poli, G. (Chem. – Eur. J., 2017)

(untitled) - Siopa, F.; Ramis Cladera, V.-A.; Afonso, C. A. M.; Oble, J.; Poli, G. (Eur. J. Org. Chem., 2018)

(untitled) - Ravasco, J. M. J. M.; Monteiro, C. M.; Siopa, F.; Trindade, A. F.; Oble, J.; Poli, G.; Simeonov, S. P.; Afonso, C. A. M. (ChemSusChem, 2019)

(untitled) - Sala, R.; Roudesly, F.; Veiros, L. F.; Broggini, G.; Oble, J.; Poli, G. (Adv. Synth. Catal., 2020)

(untitled) - Gupta, K.; Rai, R. K.; Singh, S. K. (ChemCatChem, 2018)

(untitled) - Mariscal, R.; Maireles-Torres, P.; Ojeda, M.; Sádaba, I.; López Granados, M. (Energy Environ. Sci., 2016)

(untitled) - Karlinskii, B. Y.; Ananikov, V. P. (ChemSusChem, 2021)

(untitled) - Curpanen, S.; Poli, G.; Perez-Luna, A.; Oble, J. (Asian J. Org. Chem., 2022)

(untitled) - Piutti, C.; Quartieri, F. (Molecules, 2013)

(untitled) - Verrier, C.; Moebs-Sanchez, S.; Queneau, Y.; Popowycz, F. (Org. Biomol. Chem., 2018)

(untitled) - Ghosh, A. K.; Brindisi, M. (RSC Adv., 2016)

(untitled) - Curpanen, S.; Poli, G.; Oble, J.; Perez-Luna, A. (Eur. J. Org. Chem., 2021)

(untitled) - Yang, W.; Sen, A. (ChemSusChem, 2011)
See for the synthesis of 5-methylfurfural from biomass-derived carbohydrates.

(untitled) - Kazancioglu, E. A.; Kazancioglu, M. Z.; Fistikci, M.; Secen, H.; Altundas, R. (Org. Lett., 2013)

(untitled) - Hashmi, A. S. K.; Häffner, T.; Yang, W.; Pankajakshan, S.; Schäfer, S.; Schultes, L.; Rominger, F.; Frey, W. (Chem. – Eur. J., 2012)

(untitled) - Lebœuf, D.; Schulz, E.; Gandon, V. (Org. Lett., 2014)

(untitled) - Bures, E.; Spinazzé, P. G.; Beese, G.; Hunt, I. R.; Rogers, C.; Keay, B. A. (J. Org. Chem., 1997)

(untitled) - Devarie-Baez, N. O.; Kim, W.-S.; Smith, A. B., III; Xian, M. (Org. Lett., 2009)

(untitled) - Taguchi, H.; Ghoroku, K.; Tadaki, M.; Tsubouchi, A.; Takeda, T. (Org. Lett., 2001)

(untitled) - Taguchi, H.; Ghoroku, K.; Tadaki, M.; Tsubouchi, A.; Takeda, T. (J. Org. Chem., 2002)

(untitled) - Taguchi, H.; Takami, K.; Tsubouchi, A.; Takeda, T. (Tetrahedron Lett., 2004)

(untitled) - Denmark, S. E.; Yang, S.-M. (Org. Lett., 2001)

(untitled) - Denmark, S. E.; Yang, S.-M. (Tetrahedron, 2004)

(untitled) - Gudmundsson, H. G.; Kuper, C. J.; Cornut, D.; Urbitsch, F.; Elbert, B. L.; Anderson, E. A. (J. Org. Chem., 2019)

(untitled) - Trost, B. M.; Machacek, M. R.; Ball, Z. T. (Org. Lett., 2003)

(untitled) - Denmark, S. E.; Tymonko, S. A. (J. Am. Chem. Soc., 2005)

(untitled) - Denmark, S. E.; Liu, J. H.-C. (J. Am. Chem. Soc., 2007)

(untitled) - Takeda, T.; Matsumura, R.; Wasa, H.; Tsubouchi, A. (Asian J. Org. Chem., 2014)

(untitled) - Wang, Y.; Xiao, Y.; Yang Tan, T. T.; Ng, S.-C. (Tetrahedron Lett., 2008)

(untitled) - Kim, D. W.; Jeong, H.-J.; Lim, S. T.; Sohn, M.-H. (Angew. Chem., Int. Ed., 2008)